Neuropraxia following resection of a retroperitoneal liposarcoma - Tsiao, Stevenson (Int J Surg Case Rep, 2017)
BACKGROUND: This is a unique case of neuropraxia of femoral nerve seen after resection of retroperitoneal liposarcoma which has not been reported before in the literature. INTRODUCTION: Neuropraxia, a transient paralysis due to blockage of nerve conduction, commonly associated with athletes and orthopedic procedures, has not been previously reported as a complication following resection of retroperitoneal sarcoma. CASE: This is an 81-year-old female who, on CT for evaluation of her atherosclerosis, was found to have an incidental right-sided retroperitoneal mass extending from the right renal capsule inferiorly through the inguinal canal. At this point, the patient reported mild right sided abdominal pain and right lower back pain, but reported no neuromotor deficits of the right lower extremity. Given the symptoms of the patient as well as the size, location and the density of the lesion, surgical intervention was pursued. On exploration, the lipomatous lesion, suggestive of liposarcoma, was invading the right genitofemoral nerve and ilioinguinal nerve which were sacrificed to ensure a complete oncologic resection. Following complete removal of the mass, she developed right side femoral nerve neuropraxia, suffering complete loss of motor function in the femoral distribution. Pathology revealed the mass to be a low grade liposarcoma. DISCUSSION: The patient required only physical therapy and oral prednisone following surgery for treatment of the neuropraxia. She responded well and has regained significant neuromotor function of the affected limb. Cases presenting with post-resection neurological sequelae without any known intraoperative nerve injury may respond very well to conservative treatment. Hence, it is very important to collaborate with Neurology and Physical Therapy to achieve best possible outcome.